Linking refugee influx and biofuel energy production to the nexus between fossil-fuel energy consumption and economic growth: Insights from USA and Brazil with novel Fourier VAR and causality techniques - Bildirici, Melike E.; Ersin, Ozgur Omer (ELSEVIER, 2026)
Refugees have emerged as a significant social factor in global dynamics, influencing various sectors, including energy consumption (EC), refugees were criticized for heavy reliance on fossil-fuels. Recently, biofuel energy production (BF) has attracted attention of IEA, as a low-emission alternative, USA and Brazil have promoted their BF as cleaner energy alternative. Study integrates BF and RF to nexus between EC and economic growth (EG) with novel Fourier-VAR and Fourier-Granger-causality techniques employed under structural breaks, for USA and Brazil, 1990-2023. Findings indicate significant positive effects of BF and RF on EG in both countries with different magnitudes. EG of host also appears as significant driver of RF and BF. in addition to significance of BF on EG and EC in both nations. Moreover, RF in these countries also have positive effects on EG, EC and BF, in addition to effects of RF on EC. Interrelations among EC, BF and RF confirm significance of BF development efforts. Causality tests highlight unidirectional causality from RF to BF and EC, and bidirectional causalities between BF-EC, EC-EG, BG-EG confirms feedback relations. Comparatively, findings are consistent in direction and sign, only differ in magnitude in majority. Study findings have implications on energy, refugees, and sustainable development.
Keywords: Refugee population; Renewable energy; Biofuel; Sustainable development; Fourier; Causality; UNIT-ROOT TEST; CO2 EMISSIONS; ELECTRICITY CONSUMPTION; NONRENEWABLE ENERGY; MIGRATION; PANEL; SERIES; OUTPUT; Science & Technology - Other Topics; Energy & Fuels